Mysteries of Cinema : Reflections on Film Theory, History and Culture 1982-2016 - Martin, Adrian, 1959- (Book collections on Project MUSE., 2018)
The essays of distinguished film critic Adrian Martin have long been difficult to access, so this anthology, which collects his work in one volume, will be welcomed throughout film studies. He offers in-depth analysis of many genres of films while providing a broad understanding of the history of cinema and the history of film criticism and culture. These vibrant, highly personal essays balance breadth across cinema theory with almost encyclopedic detail, ranging between aesthetics, cinephilia, film genre, criticism, philosophy, and cultural politics.